Tras las huellas del hombre americano: un enfoque parasitologico - RETANA-SALAZAR, Axel P. (Antropología Experimental, 2014)
In this work I propose the use of the BPA as a technique for the study of the biogeographical vicariance and the coevolution between species, as a techique for the evaluation of the relation among the parasites and the host. In this casethere are several morphological changes in the lice species associated to the man, this morphological changes associated with different etnies and with isolated areas permit the use of this systematic analysis to attempt to discover the possible way that man follows to America. I conclude that man come toAmerica by Bering as the traditional data sugest, but also for the South arriving possibly to the Pacific coast of South America, may be Peru or Ecuador. Some populations of lice isolated in the native peoples of the Costa Rican pacific coastleads that this hypothesis is possible.